Consumer Psychology - Hackett, Paul M.W.; Schwarzenbach, Jessica B.; Jürgens, Uta Maria (Verlag Barbara Budrich, 2022)
This book provides students with a clear and concise guide to studying undergraduate courses in qualitative consumer research and ethnography. The authors present the major qualitative research approaches used in consumer and marketing research as well as practical procedures and theoretical aspects of research design, report presentation etc. In addition to that a weekly study guide, including comprehensive reading lists, completes the book.